Role of Surface Glycoproteins in Human Platelet Function - Nurden, A. T; Caen, J. P (Thrombosis and Haemostasis, 1976)
Glycoproteins present at the external surface of cells probably play specific roles in cellular function. Increasing evidence suggests that the glycoproteins span the plasma membrane with the bulk of the bound carbohydrate asymmetrically distributed on the outer surface. Micellar association of glycoproteins in membranes leads to pore formation and functional roles in transport through the membrane, while surface glycoproteins have been shown to be enzymes, to determine cell specificity and contribute to the cell surface charge. The platelet plasma membrane contains 3 major glycoproteins, glycoproteins I, II and III as characterized in order of their decreasing molecular weight. Glycoprotein I appears to have the highest sialic acid content and to give rise to a platelet specific acidic macroglycopeptide on trypsin digestion. Specific glycoprotein abnormalities in the platelets of patients with Glanzmann’s thrombasthenia suggest that the glycoproteins play a role in the mechanism of platelet aggregation. A much reduced content of glycoprotein I in the platelets of 2 patients with the Bernard Soulier syndrome may be associated with their defective adhesion to subendothelium and indicates a possible relationship on the platelet surface with the von Willebrand factor protein. Preliminary evidence suggests that in common with other plasma membranes the platelet membrane has a fluid structure and that the organization of the glycoproteins on the platelet surface is extremely sensitive to stimuli and susceptible to change.